Data analysis with Microsoft Power BI - Larson, Brian (McGraw-Hill Education, 2020)
Publisher's Note: Products purchased from Third Party sellers are not guaranteed by the publisher for quality, authenticity, or access to any online entitlements included with the product. Explore, create, and manage highly interactive data visualizations using Microsoft Power BI Extract meaningful business insights from your disparate enterprise data using the detailed information contained in this practical guide. Written by a recognized BI expert and bestselling author, Data Analysis with Microsoft Power BI teaches you the skills you need to interact with, author, and maintain robust visualizations and custom data models. Hands-on exercises based on real-life business scenarios clearly demonstrate each technique. Publishing your results to the Power BI Service (PowerBI.com) and Power BI Report Server are also fully covered. Inside, you will discover how to: " nderstand Business Intelligence and self-service analytics " xplore the tools and features of Microsoft Power BI " reate and format effective data visualizations " ncorporate advanced interactivity and custom graphics " uild and populate accurate data models " ransform data using the Power BI Query Editor " ork with measures, calculated columns, and tabular models " rite powerful DAX language scripts " hare content on the PowerBI Service (PowerBI.com) " tore your visualizations on the Power BI Report Server